IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA SEKOLAH PENGGERAK DI KOTA PALEMBANG: STUDI KASUS SMPN 20 dan SMPN 45 PALEMBANG: Penelitian Skripsi - Novita, Dina; Chotimah, Umi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project at two Driving Schools in Palembang, namely SMPN 20 and SMPN 45. Using a mixed-methods approach, quantitative data from questionnaires measured Pancasila Student Profile Reinforcement Project understanding and the achievement of Pancasila Student Profile dimensions, while interviews and documentation provided qualitative data on the planning, implementation, and evaluation of the Pancasila Student Profile Strengthening Project. The results show that both schools achieved "very high" scores in terms of understanding and the formation of the six dimensions of the Pancasila Student Profile. A fascinating finding in this research is that the geographical location of the school does not linearly determine its quality or efficiency, but rather how the school adapts and manages during the project's implementation.